Commitment Savings Accounts in Malawi : A Product Design Case Study - International Finance Corporation (Washington, DC, 2015)
Malawi s economy is heavily dependent on agriculture, especially tobacco, which comprises a majority of the country s exports. Tobacco farmers have one harvest a year, and while their income stream occurs over several months it must last them for the entire year, making it difficult to smooth consumption throughout the year. The objective of this case study is to present the design and implementation of a commitment savings product for groups of tobacco farmers in Malawi. The product was successful in encouraging savings, increasing input purchases and yields for the next year s harvest, and increasing consumption after the harvest. The following sections describe the lack of formal savings options for rural farmers, the behavioral concept behind commitment savings accounts, the product designed to address these problems and subsequent changes to the original design, results of a field experiment evaluating the product, and lessons learned for other commitment savings products.